Penegakan Hukum Tindak Pidana Pelanggaran Lalu Lintas Melalui Tilang Elektronik di Wilayah Kota Madiun - Adelia Fatin Faadihilah; Ari Wibowo (Fakultas Hukum Universitas Islam Indonesia, 2023)
This research concerns law enforcement of traffic violations through electronic ticketing in the Madiun City Region. This type of research uses empirical legal research. This study uses a statutory approach and a sociological approach. The results of the study are that, first, law enforcement against electronic traffic ticket violations in the Madiun City Region is carried out with preventive efforts in the form of police goes to school and Podcast Influencer activities. Meanwhile, a repressive effort is to follow up on traffic violators massively through the help of CCTV which catches traffic violators in Madiun City. Second, the obstacle in law enforcement against electronic traffic ticket violations in the Madiun City Region is that the e-ticket regulations have not been made by the Madiun City Government; The Back Officer cannot process the results of camera work in the form of detecting vehicle license plates; the people of Madiun City are mostly still ignorant of traffic regulations; and the socialization of e-tickets is still lacking in its implementation.